1982
DOI: 10.1159/000173546
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology of Tiapamil in Concealed Accessory Pathways

Abstract: The effect of 2 mg/kg intravenous tiapamil was studied by programmed stimulation of the heart in 6 patients. Before tiapamil, sustained tachycardias were initiated in 5, and only atrial echoes in 1. In all patients, the reentrant circuit involved an accessory pathway conducting only in the ventriculoatrial direction. When administered during tachycardia, tiapamil promptly terminated the arrhythmia in 5 cases. Tiapamil lengthened the atrio-His (A-H) interval and the effective refractory period of the A-V node. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1982
1982
1991
1991

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…in the dose of 1.5 mg/kg i.v.. the HR. These findings confirm those obtained by other investigators in different patients [1][2][3]. The effects of the 1.5 mg/kg dose are more marked than those of the lower dose (1 mg/kg), showing a correlation be tween the dose and the effect.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…in the dose of 1.5 mg/kg i.v.. the HR. These findings confirm those obtained by other investigators in different patients [1][2][3]. The effects of the 1.5 mg/kg dose are more marked than those of the lower dose (1 mg/kg), showing a correlation be tween the dose and the effect.…”
Section: Discussionsupporting
confidence: 91%
“…Seipel and Breithardt [1] have re viewed the electrophysiological properties of calcium antagonists. Other authors have de scribed the electrophysiological effects of tia pamil in patients with concealed accessory' pathways [2] and also in patients with differ ent cardiac diseases [3].…”
Section: Introductionmentioning
confidence: 99%
“…a congener of verapamil, has been shown to be useful in the management of paroxysmal reentrant supraventricular ta chycardia 11,2], The present study extends 1 Supported by the Fonds zur Förderung der wissen schaftlichen Forschung in Österreich, project 4011.…”
Section: Introductionsupporting
confidence: 69%
“…Our first study on the elec trophysiology of this calcium antagonist in normal subjects showed a prolongation of the functional and effective refractory' periods of the A-V node [4], On this basis one may pre dict that tiapamil could well be as potent in terminating A-V nodal reentrant tachycar dias as verapamil which is regarded as the most potent drug available for this purpose [6,8,9]. All tachycardias due to reentry in the A-V node alone or in the A-V node and a concealed accessory connection were inter rupted within 2 min [1,2], The present re sults extend this favorable action to circus movement tachycardia in the overt antegrade preexcitation syndrome. Both orthodromic and antidromic (limited data) tachycardias responded favorably.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation